Detection of Mycobacterium avium subsp. paratuberculosis by a Direct In Situ PCR Method - Fernando Delgado; Diana Aguilar; Sergio Garbaccio; Gladys Francinelli; R. Hernández-Pando; María Isabel Romano (Veterinary Medicine International)
In situ detection of Mycobacterium avium subsp. paratuberculosis is useful for diagnosis and research of paratuberculosis. The aim of this paper was to detect this agent in formalin-fixed, paraffin-embedded tissue samples by a direct in situ PCR. The technique was performed on ileum or ileocaecal lymph node samples from 8 naturally infected cattle and 1 healthy calf, by using p89 and p92 primers for amplification of IS900 sequence. Moderate positive signal was detected in all positive samples and not in negative control, but tissues resulted were affected in many cases due to the enzymatic treatment and the high temperature exposition. Although the technique was useful for Map detection, the signal was lower than immunohistochemistry probably because of the fixation process. In one case, signal was higher, which might be due to the detection of spheroplasts. Thus, the described method should be recommended when others resulted negative or for spheroplasts detection.